Pengaruh Rotasi Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Graha Andrasentra Propertindo, Tbk - Fahmi Junaedi; Muhammad Azis Firdaus; Anuraga Kusumah (CV. ITTC INDONESIA, 2024)
The purpose of this research is to see the effect of work rotation and work motivation on the performance of PT employees. Graha Andrasentra Propertindo, Tbk, either partially or simultaneously. This research uses a quantitative approach and data collection techniques using questionnaires, with a sample of all employees totaling 50 respondents. The results of the multiple regression analysis test are Y = 5.810 + 0.315 X1 + 0.533 X2. The results of the correlation test have an interval between (0.800 - 1.000), and the determination test has a contribution of variables X1 to Y of 71.2%, X2 to Y of 76.8%, and together X1 and X2 to Y of 80 .3%, which means the independent variable has a strong and positive relationship with the dependent variable. The results of the work rotation t test showed that t count > t table (10.899 > 2.010) meaning that Ho1 was rejected and Ha1 was accepted, the work motivation t test obtained results of (12.608 > 2.010) meaning that Ho2 was rejected and Ha2 was accepted, and the f test result was (95.809 > 3.18) means Ho3 is rejected and Ha3 is accepted. From these data it can be concluded that work rotation and work motivation influence the performance of PT employees. Graha Andrasentra Propertindo, Tbk partially and simultaneously.